Rethinking Nigeria’s Security Threats: Armed Banditry and its Impacts on the People of North-west Nigeria, 2010-2025 - ESAMAGU, Efemena Emmanuel; ADEYINKA, Taiwo Adebayo (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This discourse which is intended to contribute to peace and security studies examined the effects of armed banditry on the people of North-western Nigeria. The paper answered these questions: Who are armed bandits? What is the modus operandi (mode of operations) of these bandits? How has banditry affected the people in North-west Nigeria? Different materials were reviewed and they associated armed banditry with the level of economic underdevelopment and infrastructural decay in the region viz-a-viz the influx of criminal elements, proliferation of small arms and light weapons, etc. The sociological and queer ladder theories were advanced and employed to explain the rationale behind the abnormal behavior of these terrorists as adduced. The inability of the military not only to de-escalate this violence but to curtail the activities of these armed bandits is responsible for mass abduction and kidnapping of people for ransom within the context of this study. Oral interviews were conducted to give fillip to the interdisciplinary nature of the paper, considering the avalanche of literature consulted across different disciplines. The paper’s submission is that the attendant woes of armed banditry on the people are incalculable in terms of humans, environment, economy, distortion and dislocation of families, among other attendant consequences. The paper recommended the continuous need for synergy among the security agencies while there is a need for protection of the citizens, considering the wave of insecurity in North-west Nigeria.